2011
DOI: 10.3390/ijms13010240
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Whey Protein Isolate with Supercritical Carbon Dioxide—Process Modeling and Cost Estimation

Abstract: An economical and environmentally friendly whey protein fractionation process was developed using supercritical carbon dioxide (sCO2) as an acid to produce enriched fractions of α-lactalbumin (α-LA) and β-lactoglobulin (β-LG) from a commercial whey protein isolate (WPI) containing 20% α-LA and 55% β-LG, through selective precipitation of α-LA. Pilot-scale experiments were performed around the optimal parameter range (T = 60 to 65 °C, P = 8 to 31 MPa, C = 5 to 15% (w/w) WPI) to quantify the recovery rates of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Some examples are: protein fractionation of skim milk by means of microfiltration 16 , purification of β-casein using cross-flow polymeric microfiltration membranes 17 , fractionation of α s -casein, κ-casein and β-casein 18 , concentration of milk proteins using negatively-charged ultrafiltration membranes 19 and supercritical carbon dioxide to effectively fractionate whey proteins (α-lactalbumin and β-lactoglobulin), as well as to isolate casein glycomacropeptide (an amino acid fragment of κ-casein) 20,21 . Some examples are: protein fractionation of skim milk by means of microfiltration 16 , purification of β-casein using cross-flow polymeric microfiltration membranes 17 , fractionation of α s -casein, κ-casein and β-casein 18 , concentration of milk proteins using negatively-charged ultrafiltration membranes 19 and supercritical carbon dioxide to effectively fractionate whey proteins (α-lactalbumin and β-lactoglobulin), as well as to isolate casein glycomacropeptide (an amino acid fragment of κ-casein) 20,21 .…”
Section: Fractionation Of Milk and Production Of Milk Proteinsmentioning
confidence: 99%
“…Some examples are: protein fractionation of skim milk by means of microfiltration 16 , purification of β-casein using cross-flow polymeric microfiltration membranes 17 , fractionation of α s -casein, κ-casein and β-casein 18 , concentration of milk proteins using negatively-charged ultrafiltration membranes 19 and supercritical carbon dioxide to effectively fractionate whey proteins (α-lactalbumin and β-lactoglobulin), as well as to isolate casein glycomacropeptide (an amino acid fragment of κ-casein) 20,21 . Some examples are: protein fractionation of skim milk by means of microfiltration 16 , purification of β-casein using cross-flow polymeric microfiltration membranes 17 , fractionation of α s -casein, κ-casein and β-casein 18 , concentration of milk proteins using negatively-charged ultrafiltration membranes 19 and supercritical carbon dioxide to effectively fractionate whey proteins (α-lactalbumin and β-lactoglobulin), as well as to isolate casein glycomacropeptide (an amino acid fragment of κ-casein) 20,21 .…”
Section: Fractionation Of Milk and Production Of Milk Proteinsmentioning
confidence: 99%
“…It has also been successfully used to recover proteins from whey and concentrate S. Ortega-Requena et al Journal of Biomaterials and Nanobiotechnology protein fractionation of skim milk by means of microfiltration [101], purification of β-casein using cross-flow polymeric microfiltration membranes [102], fractionation of α s -casein, κ-casein and β-casein [103], concentration of milk Journal of Biomaterials and Nanobiotechnology proteins using negatively-charged ultrafiltration membranes [104] and supercritical carbon dioxide to effectively fractionate whey proteins (α-lactalbumin and β-lactoglobulin), as well as to isolate casein glycomacropeptide (an amino acid fragment of κ-casein) [105] [106].…”
Section: Membrane Processesmentioning
confidence: 99%
“…However, supercritical fluids were seldom applied to fractionate biopolymers. Bonnaillie and colleagues obtained enriched ␣-lactalbumin and ␤-lactoglobulin fractions from whey protein through selective precipitation with supercritical carbon dioxide (scCO 2 ) Yver, Bonnaillie, Yee, McAloon, & Tomasula, 2012). Lee et al (2012) reported that the chitosan was extracted by static supercritical carbon dioxide (SCO 2 ) containing 1 wt% acetic acid solution as cosolvent, and the extracted chitosan displayed higher DD, lower weight-average molecular weight (Mw) and PDI than raw chitosan.…”
Section: Introductionmentioning
confidence: 99%